Toxoplasma gondii in edible fishes captured in the Mediterranean basin. (6th July 2019) - Marino, Anna Maria Fausta; Giunta, Renato Paolo; Salvaggio, Antonio; Castello, Annamaria; Alfonzetti, Tiziana; Barbagallo, Antonio; Aparo, Alessandra; Scalzo, Fabrizio; Reale, Stefano; Buffolano, Wilma; Percipalle, Maurizio
Abstract: The issue of whether market fish can be involved in the transmission of Toxoplasma gondii in the marine environment is highly debated since toxoplasmosis has been diagnosed frequently in cetaceans stranded along the Mediterranean coastlines in recent times. To support the hypothesis that fishes can harbour and effectively transmit the parasite to top‐of‐the‐food‐chain marine organisms and to human consumers of fishery products, a total of 1, 293 fishes from 17 species obtained from wholesale and local fish markets were examined for T. gondii DNA. Real‐time PCR was performed in samples obtained by separately pooling intestines, gills and skin/muscles collected from each fish species. Thirty‐two out of 147 pooled samples from 12 different fish species were found contaminated with T. gondii DNA that was detected in 16 samples of skin/muscle and in 11 samples of both intestine and gills. Quantitative analysis of amplified DNA performed by both real‐time PCR and digital PCR (dPCR) confirmed that positive fish samples were contaminated with Toxoplasma genomic DNA to an extent of 6.10 × 10 −2 to 2.77 × 10 4  copies/ml (quantitative PCR) and of 1 to 5.7 × 10 4  copies/ml (dPCR). Fishes are not considered competent biological hosts for T. gondii ; nonetheless, they can be contaminated with T. gondii oocysts flowing via freshwater run‐offs (untreated sewage discharges, soil flooding) into the marine environment, thus acting as mechanical carriers. Although the detection of viable and infective T. gondii oocysts was not the objective of this investigation, the results here reported suggest that fish species sold for human consumption can be accidentally involved in the transmission route of the parasite in the marine environment and that the risk of foodborne transmission of toxoplasmosis to fish consumers should be further investigated.